ANALISIS VEGETASI POHON DAERAH TANGKAPAN AIR WONOSADI KABUPATEN GUNUNG KIDUL - Fitriah, Umi Novita; Hadisusanto, Suwarno (Scripta Biologica, 2022)
Water is a basic necessity for living things. The catchment area (DTA) is very important to be conserved to maintain water availability and prevent the exploitation of springs. Studies on water and land conservation in Beji Village, Ngawen Sub-district are still very limited, especially DTA outside Wonosadi indigenous forest area. This study aims to study structure and composition of tree vegetation in DTA Wonosadi, Gunungkidul. Determination of DTA analyzed by using ArcGIS 10.2 with overlay of Hydrogeology Map, Indonesian Earth Map (RBI), and QuickBird Image. Analysis of vegetation in the analysis using Microsoft Excel software. Tree vegetation analysis used 10 m x 10 m square plot (40 plots) on each vegetation density class of DTA. The results showed that area of DTA Wonosadi was 23.300.924 m2. S. macrophylla King has highest density overall. S. macrophylla King, Tectona grandis L and Tectona grandis L has the highest Importance Value Index (IVI) of each vegetation class. This research concluded that tree vegetation structure in DTA Wonosadi is dominated by poles growth form. Tectona grandis L. is species that has the highest INP, which potentially affect ground water availability and reduce water discharge.